1974
DOI: 10.1254/jjp.24.57
|View full text |Cite
|
Sign up to set email alerts
|

Secretory and Vascular Response to Various Biogenic and Foreign Substances of the Perfused Canine Pancreas

Abstract: Japan. Abstract-Secretoryand vascular responses to various biogenic and foreign sub stances of the isolated blood-perfused canine pancreas were investigated. The ma jority of cholinergic drugs such as acetylcholine, methacholine, carbachol, bethanechol pilocarpine, neostigmine, lobeline, nicotine, TMA and McN-A-343, and gastroin testinal hormones such as secretin, pancreozymin, gastrin, glucagon caused an increase of output of pancreatic juice with vasodilatation.Bradykinin and kallikrein in hibited the secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Hashimoto and collaborators demonstrated that exogenous dopamine increases the secretion of pancreatic juice, of which the components are similar to those induced by exogenous secretin (2), and that there are specific dopamine receptors related to the exocrine pancreatic secretion in dogs (3)(4)(5)(6). Thus, the dopamine receptor response can be easily quantified by measuring the increases in volume of the pancreatic juice.…”
mentioning
confidence: 99%
“…Hashimoto and collaborators demonstrated that exogenous dopamine increases the secretion of pancreatic juice, of which the components are similar to those induced by exogenous secretin (2), and that there are specific dopamine receptors related to the exocrine pancreatic secretion in dogs (3)(4)(5)(6). Thus, the dopamine receptor response can be easily quantified by measuring the increases in volume of the pancreatic juice.…”
mentioning
confidence: 99%
“…Case and Scratcherd (10) reported that the secretory response to secretin was accompanied by an increase in the cytoplasmic levels of cyclic AMP. Dibutyryl cyclic AMP given intra-arterially also caused the secretion of pancreatic juice (2). These results suggest that cyclic AMP acts as a second messenger or a mediator of secretin.…”
mentioning
confidence: 67%
“…This preparation is convenient as a tool for studying the direct actions of drugs on the pancreas (2). Recently, we reported that a potent vasodilator, papaverine, caused a secretion of pancreatic juice in dogs (3).…”
mentioning
confidence: 99%
“…(20), and also showed that the dog and rat exocrine pancreas responded differently to 5-HT and histamine. On the basis of data reported thus far (7,9,20,21, and present results), the main differences between dogs and rats in the response to various amines can be summarized as follows: 1) DA has a potent stimulatory effect in dogs while DA has only a weak stimulatory effect on the protein secretion and a very weak stimulatory effect on the rate of flow in rats, 2) 5-HT has inhibitory effects on the rate of flow and protein secretion in rats, but no effect in dogs, 3) o-agonists decrease the rate of flow in rats, but have no effects in dogs, 4) j-agonist has a profound stimulatory effect on the rate of flow in rats, but has no effect in dogs, and 5) histamine is a effective stimulant in dogs, but not in rats.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, the receptor mechanism for the rate of flow could not be clarified. However, it is apparent that the stimulatory effects of DA on the exocrine pancreas in rats are weak as opposed to the strong secretin-like effects in dogs (7,(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%